Neoichnological study of two species of burrowing darkling beetles (Coleoptera: Tenebrionidae) from larval to adult stages. Issue 4 (2nd October 2021) - Thacker, Hayden A.; Hembree, Daniel I.
ABSTRACT: Beetles (Coleoptera) are a critical component of terrestrial ecosystems filling numerous ecological roles. Soil-dwelling beetles play an important role in pedogenesis through the production of biogenic structures throughout their life cycle. Given their life habits, beetle trace fossils should be abundant in the fossil record and a number of ichnotaxa have been attributed to beetles, yet there is still much to learn about their trace-making techniques and the variety of morphologies of traces they can produce throughout their life cycle. The Tenebrionidae (darkling beetles) is a common, globally distributed group that includes many soil-dwelling species from a variety of environments. The purpose of this project was to gain a better understanding of biogenic structures produced during each life stage of two species of burrowing darkling beetles, Zophobas morio F. and Tenebrio molitor L. Single to multiple specimens of each species were placed in variably sized enclosures filled with massive and layered sediment with and without layers of food. Biogenic structures produced by the two species were similar, but distinct between each life stage and associated with different behaviors. Observed biogenic structures are comparable to Palaeophycus, Planolites, Fictovichnus, Rebuffoichnus, Pallichnus, Taenidium, Skolithos, and Conichnus depending on the life stage. Neoichnological studies such as this can aid in the understanding of biogenic structures in the fossil record. Being able to effectively link continental traces to trace makers will ultimately improve our understanding of the composition of ancient terrestrial ecosystems.